I love Korean 1 - 사랑해요 한국어 1 Student's Book (서울대학교출판문화원 Viện văn hóa xuất bảnTrường ĐH Seoul, 2019)
The series of short-term (about 60 hours) Korean textbooks developed by the Seoul National University Language Education Center aim to enable adult learners to acquire basic Korean language skills in a short period of time.